COMPARATIVE OF EXCISE STAMP PROCUREMENT USING EOQ AND JIT METHODS - Purnomo; Amodha, Javas Hasthoka (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to compare the efficiency of the Economic Order Quantity (EOQ) and Just in Time (JIT) methods in managing the procurement of excise stamps at PR. Bako Gayo, a cigarette factory in Central Aceh. Using a quantitative descriptive approach, data were obtained through documentation from the SAC Online system and analyzed using EOQ and JIT models to calculate optimal order quantity, order frequency, and total inventory cost. The results show that the EOQ method produced a total inventory cost of Rp 259,272.73, while the JIT method resulted in a significantly lower cost of Rp 97,995.88. These findings indicate that JIT provides greater cost efficiency by minimizing order frequency and holding costs while ensuring compliance with excise regulations. The results confirm previous empirical research highlighting the superiority of JIT in optimizing inventory management under inflationary and regulatory constraints. Based on the research findings, it is recommended that PR. Bako Gayo implement the Just in Time (JIT) method as the primary strategy for procuring excise stamps, as it has proven to be more efficient than the EOQ method. The implementation of JIT needs to be supported by strong coordination with suppliers and an integrated digital inventory monitoring system to ensure smooth production and compliance with excise regulations. This study contributes theoretically by extending inventory management analysis to regulated industries and provides practical and policy insights for improving efficiency in the tobacco sector. Keywords: Economic Order Quantity (EOQ), Just in Time (JIT), inventory management, excise stamps, cost efficiency